Quantum mechanics : non-relativistic theory - Landau, L. D. 1908-1968; Lifshit︠s︡, E. M. (Landau, L. D. (Lev Davidovich), 1908-1968. Teoreticheskai︠a︡ fizika (Izd. 3-e)., 1977)
This edition has been completely revised to include some 20% of new material. Important recent developments such as the theory of Regge poles are now included. Many problems with solutions have been added to those already contained in the book.